2015
DOI: 10.1039/c5md00178a
|View full text |Cite
|
Sign up to set email alerts
|

Alkylamino derivatives of N-benzylpyrazine-2-carboxamide: synthesis and antimycobacterial evaluation

Abstract: A series of alkylamino derivatives of N-benzylpyrazine-2-carboxamide was designed, synthesized and assayed in vitro for their antimycobacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…For alkyl derivatives 9 – 12 , the antimycobacterial and antibacterial activities increase with the increase in the length of the carbon chain. This is in concordance with relationships observed in our previous series of pyrazinamide derivatives [26,27,28,29]. The most active compound against Mtb was compound 17 (phenyl derivative, R’ = 2,4-diOCH 3 ) with MIC = 12.5 µg/mL, 46 µM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For alkyl derivatives 9 – 12 , the antimycobacterial and antibacterial activities increase with the increase in the length of the carbon chain. This is in concordance with relationships observed in our previous series of pyrazinamide derivatives [26,27,28,29]. The most active compound against Mtb was compound 17 (phenyl derivative, R’ = 2,4-diOCH 3 ) with MIC = 12.5 µg/mL, 46 µM.…”
Section: Discussionsupporting
confidence: 90%
“…Based on our experience from the previously published series of alkylamino substituted pyrazinamide derivatives, the antimycobacterial activity was highest for compounds possessing side chains with six to eight carbons [26,27,28,29]. In the alkyl derivatives presented in this paper (compounds 9 – 12 ), octylamide (compound 12 : MIC = 25 µg/mL, 100 µM) exerted the highest activity, followed by heptylamide ( 11 : MIC = 50 µg/mL, 212 µM) and hexylamide ( 10 : MIC = 100 µg/mL, 450 µM).…”
Section: Resultsmentioning
confidence: 99%
“…Based on molecular docking studies, various N -benzylpyrazine-2-carboxamides have been previously suggested as potential inhibitors of mycobacterial enoyl-ACP-reductase (InhA) [ 4 ], an essential enzyme in the synthesis of mycolic acids and the primary target of the first-line antitubercular isoniazid. In such PZA derivatives, the carbonyl oxygen of the carboxamide moiety was predicted to form an H -bond network to Tyr158 and 2′-OH of the ribose of the NAD + cofactor, which is a typical interaction pattern for most of the direct InhA inhibitors derived from triclosan [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of new TB cases that were multidrug-resistant (MDR-TB) was 3.3% in 2014, whereas HIV-positive patients represented 12% of the 9.6 million people who developed TB [ 3 ]. Pyrazinamide (PZA), as a fist-line antitubercular drug, has gained an irreplaceable role in TB therapy and has been subjected to various chemical modifications [ 4 , 5 , 6 , 7 ]. Although PZA has been used for over sixty years [ 8 ], it is still not completely known how PZA acts in a mycobacterial cell [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This work deals with benzylamino derivatives since compounds containing a benzylamino moiety were previously reported as anti-infective substances. N -Benzylpyrazine-2-carboxamides (i.e., containing a benzylamino moiety attached to the pyrazine nucleus via a carbonyl linker) were reported by Servusova et al to show moderate antitubercular activities [ 13 , 14 , 15 ]. Benzylamino derivatives of pyrazine (with a benzylamino moiety attached directly to the pyrazine core) reported by Zitko et al and Jandourek et al showed moderate activities as well [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%